Preliminary study for testing the significance of butyl–iso–butyl phthalate in ‎controlling faba bean broomrape - Hani Saudy; Mohamed Hamed; Ibrahim El–Metwally; Khaled Ramadan; Karam Aisa (Arab Universities Journal of Agricultural Sciences, 2019)
Due to deleterious impacts of broomrapes against the host plants, its combating is ‎essential for sustaining crop productivity. Thus, two–year field trail was conducted at ‎El Nubaria experimental farm, National Research Centre, Egypt, on two faba bean ‎genotypes (Misr–3 and Sakha–1) to investigate the importance of butyl–iso–butyl ‎phthalate as an activator for broomrape germination in comparison to glyphosate and ‎unweeded. Findings revealed that glyphosate in 2015/16 and 2016/17 seasons in ‎addition to butyl–iso–butyl phthalate in 2016/17 season caused significant reductions ‎in broomrape biomass and numbers of broomrape–infected faba bean plants plot−1 ‎compared to the unweeded. Plots of Misr–3 genotype treated with butyl–iso–butyl ‎phthalate in both season as well as plots of Misr–3 or Sakha–1 sprayed by glyphosate ‎in the first season achieved the maximum seed yield of faba bean. Since butyl–iso–‎butyl phthalate exhibits suicidal germination of broomrape seeds, it can be exploited ‎as an effective and helpful tool in integrated management programs of broomrape in ‎faba bean fields. ‎ Due to deleterious impacts of broomrapes against the host plants, its combating is ‎essential for sustaining crop productivity. Thus, two–year field trail was conducted on ‎two faba bean genotypes (Misr–3 and Sakha–1) to investigate the importance of ‎butyl–iso–butyl phthalate as an activator for broomrape germination in comparison to ‎glyphosate and unweeded. The trail design was a strip–plot in completely randomized ‎block design in six replications. Genotypes occupied the vertical main plots as well as ‎broomrape control treatments distributed in horizontal ones. Results showed that ‎broomrape biomass and numbers of broomrape–infected faba bean plants plot−1 ‎markedly responded to weed control and genotype and their interaction in both ‎seasons, except numbers of broomrape–infected plants of faba bean genotypes plot−1 ‎in 2016/17 season. Also, findings revealed that glyphosate in 2015/16 and 2016/17 ‎seasons in addition to butyl–iso–butyl phthalate in 2016/17 season caused significant ‎reductions in broomrape biomass and numbers of broomrape–infected faba bean ‎plants plot−1 compared to the unweeded. In plots of Misr–3 or Sakha–1, glyphosate ‎was the potent practice for reducing broomrape biomass and numbers of broomrape–‎infected faba bean plants plot−1 in 2015/16 and 2016/17 seasons, with no significant ‎differences with butyl–iso–butyl phthalate application in 2016/17 season. There were ‎no noticeable variations between weeded practices and genotypes and their interaction ‎on total dry weight of faba bean plants estimated at 105 DAS, in both seasons, except ‎glyphosate x Misr–3 interaction in the first season only. Plots of Misr–3 genotype ‎treated by butyl–iso–butyl phthalate in both season as well as plots of Misr–3 or ‎Sakha–1 sprayed by glyphosate in the first season achieved the maximum seed yield ‎of faba bean. Since butyl–iso–butyl phthalate causing suicidal germination of ‎broomrapes seeds, it can be exploited as an effective and helpful tool in broomrape ‎management programs in faba bean fields. Genotype; Orobanche spp; Parasitic ‎weeds; Suicidal germination; Vicia faba ‎